2016
DOI: 10.26740/parama.v3i2.1535
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Approaches to Action Research

Abstract: Action research atau penelitian tindakan kelas (PTK) merupakan upaya para pendidik yang reflektif untuk meningkatkan kualitas pengajarannya sehingga hasil pembelajaran siswa juga semakin baik. Pada awal perkembangannya di Amerika Serikat di awal abad 20, PTK menggunakan pendekatan kualitatif. Namun seiring berjalannya waktu, masalah di bidang pendidikan dan pengajaran juga semakin kompleks sehingga beberapa pendidik mulai menggunakan pendekatan kuantitatif. Makalah ini bertujuan untuk memaparkan PTK dengan pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The results also showed that using indigenous artefacts really supported conceptual field approach to learning special trigonometric angles in Table 8. Again, the results in Table 8 confirmed that the tests on the use of 30 o -60 o -90 o and 45 o -45 o -90 o related to each other (Kusumarasdyati, 2016). Drawing on the research findings of Ngu and Phan (2020), mental representations of three variant theories and mapping of two twin concepts in trigonometry is the best milieu for classroom discourse.…”
Section: Question 2: What Artefacts Do Student-teachers Use and How T...supporting
confidence: 56%
See 2 more Smart Citations
“…The results also showed that using indigenous artefacts really supported conceptual field approach to learning special trigonometric angles in Table 8. Again, the results in Table 8 confirmed that the tests on the use of 30 o -60 o -90 o and 45 o -45 o -90 o related to each other (Kusumarasdyati, 2016). Drawing on the research findings of Ngu and Phan (2020), mental representations of three variant theories and mapping of two twin concepts in trigonometry is the best milieu for classroom discourse.…”
Section: Question 2: What Artefacts Do Student-teachers Use and How T...supporting
confidence: 56%
“…The resign design primarily adopted both the quantitative and the qualitative methodologies on the conceptual field's framework in identifying the classroom problem, developing and implementing a plan, collecting and analyzing data, and making instructional decisions to share the results. Kusumarasdyati (2016) opines that action research design can be either qualitative or quantitative, within the interpretative paradigm and positivism paradigm respectively. In this study, the researcher use one group rather than assigning the class into two groups and administer a pretest and a posttest to obtain information about the effectiveness (Kusumarasdyati, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This methodology empowers the researcher to delve beneath the surface and attain a profound understanding of the subject matter and maintaining the Integrity of the Specifications. [14] III. RESULT AND DISCUSSION From all the problems that the author has described, the author provides an appropriate alternative solution to overcome these problems.…”
Section: [3][4][5][6][8]mentioning
confidence: 99%